The Development of Augmented Reality (AR)-Based Mobile Learning Media on Routing Concept Subject of Network Infrastructure Administration - Noviana Nur Rizki; Agus Efendi; Dwi Maryono (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2024)
This study aims to develop and observe the eligibility level of Augmented Reality (AR)-based mobile learning media for the routing concept in the Network Infrastructure Administration subject for Vocational School students. This research was backgrounded by the students' difficulties in understanding the simple routing procedure due to the less attractive interface and complexity of the learning media they used. The research methodology used in this study is research and development (R&D) with the Alessi & Trollip development model, which is divided into three steps: planning, design, and development. The eligibility level of the learning media was obtained from two types of tests in the development step: the alpha test (subject expert test and media expert test) and the beta test (limited user test). The results of this research show that the Augmented Reality (AR)-based mobile learning media on the routing concept for the Network Infrastructure Administration subject for Vocational School students is already good, more appealing, and can help students understand the routing concept. Based on the data analysis of the alpha-test and beta-test results, the eligibility level of the learning media is